Role of serotonin in fish reproduction - Prasad, Parvathy; Ogawa, Satoshi; Parhar, Ishwar S. (Frontiers in Neuroscience, 2015)
The neuroendocrine mechanism regulates reproduction through the hypothalamo-pituitary-gonadal (HPG) axis which is evolutionarily conserved in vertebrates. The HPG axis is regulated by a variety of internal as well as external factors. Serotonin, a monoamine neurotransmitter, is involved in a wide range of reproductive functions. In mammals, serotonin regulates sexual behaviours, gonadotropin release and gonadotropin-release hormone (GnRH) secretion. However, the serotonin system in teleost may play unique role in the control of reproduction as the mechanism of reproductive control in teleosts is not always the same as in the mammalian models. In fish, the serotonin system is also regulated by natural environmental factors as well as chemical substances. In particular, selective serotonin reuptake inhibitors (SSRIs) are commonly detected as pharmaceutical contaminants in the natural environment. Those factors may influence fish reproductive functions via the serotonin system. This review summarizes the functional significance of serotonin in the teleosts reproduction.